1995
DOI: 10.1287/mksc.14.4.360
|View full text |Cite
|
Sign up to set email alerts
|

Channel Coordination When Retailers Compete

Abstract: This paper explores channel coordination by a manufacturer that sells through competing retailers and that treats these retailers equally, as required by the Robinson-Patman Act. The authors show that, in general, there exists no single two-part tariff with a constant per-unit charge that will duplicate the behavioral results (i.e., prices, quantities, and channel profits) that are obtained by a vertically integrated system; that is, the channel cannot be coordinated except in the trivial cases of identical or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
179
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(182 citation statements)
references
References 9 publications
2
179
0
1
Order By: Relevance
“…Although the assumption of a simple demand function has its limitations, this linear inverse demand function has been often used in operations management (de Mesnard, 2009 and2011;Shin and Tunca, 2010;Shang et al 2015) as well as marketing research (Ingene et al, 1995;Padmanabhan et al, 1997).…”
Section: Model Formulation and Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the assumption of a simple demand function has its limitations, this linear inverse demand function has been often used in operations management (de Mesnard, 2009 and2011;Shin and Tunca, 2010;Shang et al 2015) as well as marketing research (Ingene et al, 1995;Padmanabhan et al, 1997).…”
Section: Model Formulation and Assumptionsmentioning
confidence: 99%
“…According to Jeuland and Shugan (1983), channel coordination was defined as the 6 setting of all manufacturer and retailer-related decisions at the levels that would maximise total channel profits. The literature on supply chain coordination is rich including the studies on coordinating manufacturing supply chains (Jeuland and Shugan 1983;Ingene and Parry 1995;Weng 1995;Iyer 1998;Tsay Agrawal 2004;Raju and Zhang 2005;Cai 2010) and the supply chain scenarios where service is considered (Ernst and Cohen 1992;Tsay and Arrawal 2000;Boyaci and Gallego 2004;Li et al 2011;Chen and Shen 2012;and Liu et al 2013). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these researches on the pricing competition problem focus on the following four structures: monopoly common retailer structure [6][7][8], chain-to-chain structure [4,9,10], dual channel structure [11][12][13][14], and monopoly common manufacturer structure, which is studied in this paper. The research on the monopoly common manufacturer structure was initiated by Ingene and Parry [15], considering a coordination problem in a supply chain where a manufacturer sells its products through competing retailers. Ingene and Parry [16] demonstrated that the manufacturer can generally obtain more profits by setting a unique two-part tariff wholesale pricing policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because of the well-known problem of double marginalization, a decentralized channel often results in demand recession, which leads to lower firm profits and social welfare. A good deal of research focuses on how results in a decentralized channel can be restored to those in a centralized channel through quantity discounts or two-part tariffs (Jeuland and Shugan 1983, Moorthy 1987, Ingene and Parry 1995, Raju and Zhang 2005, franchising and contracting (Lal 1990, Iyer 1998, pull promotion (Gerstner and Hess 1995), bargaining (Iyer andVillas-Boas 2003, Dukes et al 2006), trade promotions and forward buying (Cui et al 2008, Desai et al 2010, or channel members' concerns of fairness (Cui et al 2007).…”
Section: Related Literaturementioning
confidence: 99%